2023
DOI: 10.3390/ijms24043706
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia Attenuates Cortical Interneuron Loss after Cerebral Ischemia in Near-Term Fetal Sheep

Abstract: Therapeutic hypothermia significantly improves outcomes after neonatal hypoxic-ischemic (HI) encephalopathy but is only partially protective. There is evidence that cortical inhibitory interneuron circuits are particularly vulnerable to HI and that loss of interneurons may be an important contributor to long-term neurological dysfunction in these infants. In the present study, we examined the hypothesis that the duration of hypothermia has differential effects on interneuron survival after HI. Near-term fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…This suggests that subcooling treatment lasting 72 hours is more effective than 48 hours or 120 hours. [ 19 ] The target temperature for subcooling therapy is generally 2 to 4 °C below brain body temperature, with body surface temperature maintained at 33.5 to 34.0 °C. [ 20 ] Shankaran et al [ 21 ] did extensive research on moderate-to-severe neonatal HIE, exploring whether 120 hours of subcooling or a body surface temperature of 32.0 °C could reduce mortality or disability in 18-month-old infants, and ultimately concluded that subcooling for more than 72 hours or a body surface temperature as low as 33.5 °C did not further improve the mortality or disability rates of the infants.…”
Section: Subcoolingmentioning
confidence: 99%
“…This suggests that subcooling treatment lasting 72 hours is more effective than 48 hours or 120 hours. [ 19 ] The target temperature for subcooling therapy is generally 2 to 4 °C below brain body temperature, with body surface temperature maintained at 33.5 to 34.0 °C. [ 20 ] Shankaran et al [ 21 ] did extensive research on moderate-to-severe neonatal HIE, exploring whether 120 hours of subcooling or a body surface temperature of 32.0 °C could reduce mortality or disability in 18-month-old infants, and ultimately concluded that subcooling for more than 72 hours or a body surface temperature as low as 33.5 °C did not further improve the mortality or disability rates of the infants.…”
Section: Subcoolingmentioning
confidence: 99%
“…These findings suggest that perinatal hypoxia disrupts the delicate balance between excitatory and inhibitory circuits within the developing brain. Studies report a decrease in major interneuron types (Komitova, Xenos et al 2013, Chavez-Valdez, Emerson et al 2018, Stolp, Fleiss et al 2019, Yang, Davidson et al 2023). However, the functional impact of this interneuron injury on neuronal network activity and glutamatergic transmission remains unclear.…”
Section: Introductionmentioning
confidence: 99%